1998
DOI: 10.1149/1.1838640
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Lithium Metal Surface by Nonionic Polyether Surfactants: Quartz Crystal Microbalance Studies

Abstract: In order to stabilize and obtain highly ion-conductive surface films, lithium metal was modified using two kinds of nonionic polyether-type surfactants, viz., poly(ethylene glycol) dimethyl ether and dimethyl silicone/propylene oxide copolymer in propylene carbonate (PC) and ethylene carbonate (EC) + dimethyl carbonate (DMC) solutions. Impedance spectroscopy indicated that the surface films formed in the presence of these surfactants were very stable, whereas that in the absence of surfactant was not. Scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 5 publications
1
50
0
Order By: Relevance
“…Much effort has been exerted to improve the surface uniformity of SEI layers and to form electrochemically stable SEI layers. Several approaches have been pursued to improve the rechargeability and reliability of the metallic lithium electrode: i) the use of liquid or polymer electrolytes that are less reactive toward lithium electrodes; [71][72][73][74][75][76][77] ii) the protection of lithium electrodes by adding surface active agents such as hydrocarbons and quarternary ammonium salts; [ 78 , 79 ] iii) the formation of Li 2 CO 3 , LiF, LiOH, or polysulfi de by using CO 2 , [ 74 , 80-86 ] HF, [87][88][89][90] water trace, [ 74 , 81 , 91 ] and S x 2 − ; [ 80 , 92 ] iv) the formation of a stable metal alloy (LiI) by incorporating SnI 2 or AlI 3 ; [ 93 ] v) the use of surfactants such as non-ionic polyether compounds; [ 94 ] vi) uniform lithium deposition by means of pressure and temperature; [ 70 , 95 , 96 ] vii) the removal of impurities from the interface of lithium metal and electrolyte with an inorganic fi ller such as silica, alumina, zeolite, or titanate, [97][98][99][100][101][102] viii) the suppression of lithium dendrites by the formation of an ultra-thin polymer electrolyte layer based on plasma polymerization or UV irradiation polymerization. [103][104][105][106][107] The formation of a stable SEI layer on the lithium metal surface can be promoted by adding agents such as CO 2 , HF, or S x 2 − , and, thus, the dendritic lithium formation can be greatly suppressed.…”
Section: Surface Modifi Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…Much effort has been exerted to improve the surface uniformity of SEI layers and to form electrochemically stable SEI layers. Several approaches have been pursued to improve the rechargeability and reliability of the metallic lithium electrode: i) the use of liquid or polymer electrolytes that are less reactive toward lithium electrodes; [71][72][73][74][75][76][77] ii) the protection of lithium electrodes by adding surface active agents such as hydrocarbons and quarternary ammonium salts; [ 78 , 79 ] iii) the formation of Li 2 CO 3 , LiF, LiOH, or polysulfi de by using CO 2 , [ 74 , 80-86 ] HF, [87][88][89][90] water trace, [ 74 , 81 , 91 ] and S x 2 − ; [ 80 , 92 ] iv) the formation of a stable metal alloy (LiI) by incorporating SnI 2 or AlI 3 ; [ 93 ] v) the use of surfactants such as non-ionic polyether compounds; [ 94 ] vi) uniform lithium deposition by means of pressure and temperature; [ 70 , 95 , 96 ] vii) the removal of impurities from the interface of lithium metal and electrolyte with an inorganic fi ller such as silica, alumina, zeolite, or titanate, [97][98][99][100][101][102] viii) the suppression of lithium dendrites by the formation of an ultra-thin polymer electrolyte layer based on plasma polymerization or UV irradiation polymerization. [103][104][105][106][107] The formation of a stable SEI layer on the lithium metal surface can be promoted by adding agents such as CO 2 , HF, or S x 2 − , and, thus, the dendritic lithium formation can be greatly suppressed.…”
Section: Surface Modifi Cationmentioning
confidence: 99%
“…Also, when a polyether surfactant such as poly(ethylene glycol)dimethyl ether (PEGDME) was used as an additive, signifi cant suppression of the inactivation of the deposited lithium was reported. [ 94 ] It was reported that the adsorption and desorption process of the surfactants accompanying lithium deposition-dissolution makes the current density more uniform on the lithium surface.…”
Section: Surface Modifi Cationmentioning
confidence: 99%
“…It results in capacity loss, and reduces the cycling efficiency. Moreover, Li dendrites may pierce the separator and cause short circuits in batteries [3].The most popular model for the interface between Li metal and nonaqueous electrolytes, proposed by Peled, is called the solid electrolyte interface (SEI) model [4]. In the SEI model, the surface film can affect the morphology of the electrodeposited Li because Li metal is deposited via migration of Li § ions through the SEI film.…”
mentioning
confidence: 99%
“…The SEI films are known to be composed of various lithium compounds such as LiOH, Li20, and Li2CO3 [5], and therefore the as-formed SEI film has heterogeneous compositions. In the case of a rechargeable battery, the charging current distribution in such an SEI film is localized and causes dendritic growth [3].Dendritic growth of deposited Li causes the worst problem in metal rechargeable batteries; for this reason much research has been done on the prevention of Li dendrite growth. It has been said that Li dendrite growth is restrained when SEI is stable, thin, smooth and homogeneous [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation